COMPARISON USING MEDIA CARD IMAGES AND ANIMATION IN IMPROVING THE KNOWLEDGE METAMORPHOSIS OF ANIMALS IN DEAF CHILDREN - Sutisna, Nia (EDUTECH, 2016)
Abstrack, The study, entitled "comparison using the media card images and animations to improve the knowledge of animal metamorphosis in deaf children", aims to determine the differences in media use picture cards and animations based on the results of the test after the treated media. Methods This study uses a quantitative approach to experiment with the design of Counter Balance, is the rotation design allows two classes of media research to get the same treatment, as for data analysis using the Wilcoxon test. This research was conducted in class IV and V SLB Gandasari Indramayu with a total sample of eight people and made two groups according to the class. The results of the test scores after tested with Wilcoxon test calculations in may conclude that researchers propose hypotheses accepted, that there are differences in the use of media cards and animated images in increasing knowledge of animal metamorphosis in deaf children. This study is expected to be a reference to the suggestion that more and more schools are given attention on the use of the media, especially the animation of deaf children to help improve knowledge in the subject matter.Keywords: Animal Metamorphosis Knowledge, Media Card Image, Animation.Abstrak, penelitian yang berjudul â€œperbandingan menggunakan media kartu gambar dan animasi dalam meningkatkan pengetahuan metamorfosis hewan pada anak tunarunguâ€, bertujuan untuk mengetahui perbedaan penggunaan media kartu gambar dan animasi berdasarkan hasil tes setelah diberi perlakuan media tersebut. Metode penelitian ini menggunakan pendekatan kuantitatif eksperimen dengan desain Counter Balance, yaitu desain rotasi yang memungkin dua kelas penelitian mendapatkan perlakuan media yang sama, adapun analisis datanya menggunakan uji Wilcoxon. Penelitian ini dilakukan di kelas IV dan V SLB Gandasari Indramayu dengan jumlah sampel sebanyak delapan orang dan dijadikan dua kelompok sesuai kelas. Hasil skor tes setelah diuji dengan perhitungan Uji Wilcoxon didapat kesimpulan hipotesis yang peneliti ajukan diterima, yaitu terdapat perbedaan penggunaan media kartu gambar dan animasi dalam meningkatkan pengetahuan metamorfosis hewan pada anak tunarungu. Penelitian ini diharapkan dapat menjadi acuan saran bagi sekolah agar semakin lebih diberi perhatian tentang penggunaan media khususnya animasi bagi anak tunarungu untuk membantu meningkatkan pengetahuan dalam hal materi pelajaran.Kata kunci: Pengetahuan Metamorfosis Hewan, Media Kartu Gambar, Animasi.